What can we do with a dental avulsion? A multidisciplinary Clinical Protocol - Bustamante Hernández, Naia; Amengual Lorenzo, José; Fernández Estevan, Lucía; Zubizarreta Macho, Álvaro; Martinho da Costa, Cátia Gisela; Agustín Panadero, Rubén (My University, 2021)
Purpose: The aim of this case report was to explain a multidisciplinary and conservative approach carrying out the replantation of an avulsed closed apex central incisor stored in dry conditions for a 16-hour period from the moment of trauma. Case report: This report describes a case of a 28 year-old male who suffered contusion of the upper lip, avulsion of right upper central incisor, enamel cracks after trauma of left upper central incisor and upper left lateral incisor crown fracture due to an accident. Avulsed tooth was dry stored and it was replanted 16h after the trauma. The root was disinfected and the necrotic periodontal tissue removed, the endodontic treatment was done before replantation and a flexible splint was applied to tooth 13 to tooth 23. Two months later a contralateral tooth presented crown discoloration occurred due to pulp necrosis an endodontic treatment as well as bleaching were carried out. An esthetic restoration for lateral incisor crown fracture was also done. In the one year review the patient remains asymptomatic, with no signs of root resorption or ankylosis of the damaged teeth. Conclusions: A conservative approach of tooth with delayed reimplantation can be a stable and functional with the appropriate treatment procedures. A clinical protocol for patients and professionals for the treatment of the avulsed tooth is proposed.